Pelaksanaan Pengarsipan Akta Kelahiran - Rahayu Subekti; Eistetika Sari (Faculty of Law, Universitas Wijayakusuma, 2021)
This research aims to determine the implementation of archiving birth certificates at the Department Population and Civil Registration of Sukoharjo Regency, and obstacles and solutions for the Department of Population and Civil Registration of Sukoharjo Regency in the implementation of archiving birth certificates. This research is a descriptive juridical empirical legal research were carried out by interview, observation, and document study, with qualitative data analysis techniques. The approach uses a qualitative approach with primary and secondary data source. The author concludes that Department of Population and Civil Registration of Sukoharjo Regency in carrying out birth certificate archiving has not run optimally. Due to a change in the system from using digital archives to conventional archives. Each of digital and conventional archiving has obstacles and solutions to overcome. Keywords : Archiving, Birth Certificate. Abstrak. Penelitian ini bertujuan untuk mengetahui pelaksanaan pengarsipan akta kelahiran di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sukoharjo serta hambatan dan solusi bagi Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sukoharjo dalam pelaksanaan pengarsipan akta kelahiran. Penelitian ini merupakan penelitian hukum yuridis empiris bersifat deskriptif dengan mengumpulkan data melalui wawancara, observasi dan studi dokumen. Pendekatan menggunakan pendekatan kualitatif dengan sumber data primer dan sekunder, Penulis menyimpulkan bahwa Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sukoharjo dalam melaksanakan pengarsipan akta kelahiran belum optimal. Adanya perubahan sistem dari arsip digital menjadi konvensional. Dalam pengarsipan secara digital maupun konvensional masing-masing memiliki hambatan dan solusi untuk mengatasinya. Kata kunci : Pengarsipan, Akta Kelahiran.